An empirical investigation on Google Classroom: use behaviour of Malaysian school teachers - Moses, Priscilla; Chung, Jacqueline Ling Lau; Phaik, Kin Cheah; Soong, Phoebe Yee Yap; Md. Khambari, Mas Nida; Su, Luan Wong (Asia-Pacific Society for Computers in Education (APSCE), 2023)
Google Classroom (GC) has become a prominent online learning platform in Malaysia since the government’s official announcement and later sees its boost in usage again during the COVID-19 pandemic due to the implementation of emergency remote teaching. The literature has unveiled that the mean score pertaining to technological knowledge in the context of GC usage was the lowest. Therefore, this study aims to investigate the level of GC use and the significant influence of facilitating conditions, habit, and behavioural intention on GC use behaviour among Malaysian teachers. A total of 37 secondary school teachers participated in an online quantitative survey consisting of 22 five-point Likert scale items. Descriptive statistics and standard regression analysis were used to analyse the data. Findings found that the extent of agreement and utilisation of GC during the pandemic were only moderate, requiring increased focus as a precautionary measure for potential future scenarios, such as another pandemic, where remote learning becomes the sole viable option. Results also suggested habit (β = 1.128, p < .0005) as the most significant factor that influences Malaysian teachers’ GC use behaviour. Thus, future initiatives in boosting the intentions of using GC among Malaysian teachers need to be considered.